Comparison between thermophysical and tribological properties of two engine lubricant additives: electrochemically exfoliated graphene and molybdenum disulfide nanoplatelets. (12th October 2020) - Guimarey, María J G; Abdelkader, Amor M; Comuñas, María J P; Alvarez-Lorenzo, Carmen; Thomas, Ben; Fernández, Josefa; Hadfield, Mark
Abstract: Recently graphene and other 2D materials were suggested as nano additives to enhance the performance of nanolubricants and reducing friction and wear-related failures in moving mechanical parts. Nevertheless, to our knowledge there are no previous studies on electrochemical exfoliated nanomaterials as lubricant additives. In this work, engine oil-based nanolubricants were developed via two-steps method using two different 2D nanomaterials: a carbon-based nano additive, graphene nanoplatelets (GNP) and a sulphide nanomaterial, molybdenum disulfide (MoS2 ) nanoplatelets (MSNP). The influence of these nano additives on the thermophysical properties of the nanolubricants, such as viscosity index, density and wettability, was investigated. The unique features of the electrochemical exfoliated GNP and MSNP allow the formulation of nanolubricant with unusual thermophysical properties. Both the viscosity and density of the nanolubricants decreased by increasing the nanoplatelets loading. The effect of the nano additives loading and temperature on the tribological properties of nanolubricants was investigated using two different test configurations: reciprocating ball-on-plate and rotational ball-on-three-pins. The tribological specimens were analysed by scanning electron microscopy (SEM) and 3D profiler in order to evaluate the wear. The results showed significant improvement in the antifriction and anti-wear properties, for the 2D-materials-based nanolubricants as compared with the engine oil, using different contact conditions. For the reciprocal friction tests, maximum friction and worn area reductions of 20% and 22% were achieved for the concentrations of 0.10 wt% and 0.20 wt% GNP, respectively. Besides, the best anti-wear performance was found for the nanolubricant containing 0.05 wt% MSNP in rotational configuration test, with reductions of 42% and 60% in the scar width and depth, respectively, with respect to the engine oil.